1977
DOI: 10.1055/s-0028-1093563
|View full text |Cite
|
Sign up to set email alerts
|

TBG-Dependency of Age Related Variations of Thyroxine and Triiodothyronine

Abstract: Thyroxine (T4), triiodothyronine (T3) and thyroxine-binding globulin (TBG) were determined in healthy individuals ranging in age from newborn to 95 years. T4: 10.25 +/- 1.62 microng/100 ml, T3: 1.62 +/- 0.35 ng/ml and TBG: 1.34 +/- 0.15 mg/100 ml, were found elevated until puberty compared to a middle age group with T4: 7.27 +/- 2.26 microng/100 ml, T3: 1.15 +/- 0.24 ng/ml and TBG: 0.98 +/- 14 mg/100 ml. T4 and T3 followed almost TBG concentration. In old age is dissociation between T4: 5.79 +/- 1.56 microng/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2
6

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 2 publications
2
13
2
6
Order By: Relevance
“…Um estudo com idosos internados demonstrou que os níveis de FT4 diminuem com a idade, mas aumentam proporcionalmente com a gravidade da doença (41). Com relação aos níveis séricos de T3, vários estudos demonstraram uma diminuição progressiva com a idade (9,18,19,23,25,26), chegando a 5,1ng/dl por década (25), embora o T3 reverso não tenha mostrado a mesma tendência (23,26). Por outro lado, outros trabalhos não confirmaram esta tendência na queda do T3 em função da idade (14,24,27).…”
Section: Nívei Dos Hormônios Tiroideanos Tsh E Tbgunclassified
See 2 more Smart Citations
“…Um estudo com idosos internados demonstrou que os níveis de FT4 diminuem com a idade, mas aumentam proporcionalmente com a gravidade da doença (41). Com relação aos níveis séricos de T3, vários estudos demonstraram uma diminuição progressiva com a idade (9,18,19,23,25,26), chegando a 5,1ng/dl por década (25), embora o T3 reverso não tenha mostrado a mesma tendência (23,26). Por outro lado, outros trabalhos não confirmaram esta tendência na queda do T3 em função da idade (14,24,27).…”
Section: Nívei Dos Hormônios Tiroideanos Tsh E Tbgunclassified
“…Para a TBG, o envelhecimento poderia levar a aumento (19), diminuição (47) ou nenhuma alteração (23), como foi descrito em alguns estudos.…”
Section: Nívei Dos Hormônios Tiroideanos Tsh E Tbgunclassified
See 1 more Smart Citation
“…Die radioimmunchemische zu einer Unsicherheit gegenüber der TBG-BestimBestimmung von TBG hat in den letzten Jahren im-mung geführt. Wir haben daher TBG erneut hochgemer mehr zu einer wertvollen Bereicherung in der reinigt und chemisch charakterisiert, worüber an anSchilddrüsendiagnostik selbst beigetragen (3,(8)(9)(10)(11)(12)(13)(14)(15)(16). derer Stelle berichtet wird.…”
Section: Einführungunclassified
“…Normal aging in men is accompanied by a decline in testicu lar function with decrease of serum testoster one levels [4][5][6] and an increase of LH and FSH levels [5][6][7][8], although there is increasing evidence of a secondary failure of the hypo thalamic-pituitary axis [9], Most studies have shown that serum T3 decreases with age [ 10,11], although an effect of disease and not age itself on serum T3 was also suggested [12]. Serum T4 levels are either unaffected [10,11] or slightly diminished [13,14] and serum TSH levels are elevated in some relatively healthy persons over the age of 60 [11], Although hormonal changes in pa tients with severely uncontrolled, insulin-de pendent diabetes mellitus aged between 17 and 50 years have been reported [15], the changes of serum hormone levels in elderly patients with non-insulin-dependent diabetes mellitus (NIDDM) have not been clearly elu cidated. This study was undertaken to assess the influence of NIDDM on hormonal changes in elderly men.…”
Section: Introductionmentioning
confidence: 99%